2020
DOI: 10.24018/ejbmr.2020.5.5.516
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Service Quality Towards Patient Satisfaction (Comparative Study of Patients Using Telemedicine Application and Face to Face Consultation in Healthcare)

Abstract: The world today knows the use of technology in more areas of life than ever. The invention of health technology enables health workers to utilize telecommunication devices in delivering care, easing access to healthcare anywhere, anytime. Telemedicine Application is one of the rapidly developing health applications in Indonesia. This study aimed to analyze the association between quality of services, including tangibility, reliability, responsiveness, assurance, and empathy, and patient satisfaction in Telemed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
0
10
0
4
Order By: Relevance
“…If a health application is reliable when providing services to users, this will increase user confidence in the application, which will then affect their interest in adopting the application in question. Another study conducted by Tantarto et al. (2020) reveals the reliability and responsiveness of telemedicine applications in Indonesia and shows that there are still many patients who think that telemedicine is not reliable because patients cannot see the doctor's face.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a health application is reliable when providing services to users, this will increase user confidence in the application, which will then affect their interest in adopting the application in question. Another study conducted by Tantarto et al. (2020) reveals the reliability and responsiveness of telemedicine applications in Indonesia and shows that there are still many patients who think that telemedicine is not reliable because patients cannot see the doctor's face.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reveals the reliability and responsiveness of telemedicine applications in Indonesia and shows that there are still many patients who think that telemedicine is not reliable because patients cannot see the doctor's face. They feel that because doctors cannot touch their patients, they cannot provide reliable consultations ( Tantarto et al., 2020 ). According to Silalahi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The authors explained that this result was due to the lack of adequate support, professionalization, and diversification of the provided services. On the other hand, many previous researches revealed that service quality's yielding satisfactory human relations and interaction between healthcare personnel and system users can enhance the assurance of the provided services and, therefore, increase user satisfaction [ 23 , 26 ]. As a result, it is logical to hypothesize that:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adopsi Telemedicine Di Era New Normal, Made Santika Dewi dan Ni Nyoman Sunariani dimulai dari pasien mendaftar sampai diterima/dilayani oleh dokter spesialis, diharapkan dengan pelayanan melalui telemedicine di Klinik BMMC waktu tunggu tidak lebih dari batas tersebut karen a menggunakan perangkat seluler sebagai media telemedicine ini didasarkan pada fleksibilitas dan kemampuannya untuk mengakses informasi dengan cepat. Membiarkan konsumen menunggu apalagi tanpa alasan yang jelas menyebabkan persepsi yang negatif dalam kualitas pelayanan (Tantarto et al , 2020). Salah satu Informan juga memberikan tanggapannya tentang lebih memilih melakukan konsultasi via telepon dibandingkan chatting.…”
Section: Responsivenessunclassified